Acessibilidade nos portais das universidades federais: uma análise a partir do uso de Sistemas de Gerenciamento de Conteúdo - Tavares, Eliara Maria (2016)
The Law nº. 13,146 - Brazilian Law of Inclusion of People with Disabilities (Person Statute with Disabilities) - which came into effect from January 2016 reinforces the requirement of accessibility on websites maintained by the government, established for over ten years through the Decree No. 5296/2004. Through the e-GOV, the government has undertaken several actions to boost the development of websites that attend the most diverse citizens, thus allowing access to information and public services equally and without discrimination. Among these actions highlight the Accessibility Model recommendations on Electronic Government (e-MAG) and the Web Standards in Electronic Government project (e-PWG). In this context, the web portals of the Federal University have a great responsibility to make available the content and information to the entire community. This study presents the results of the evaluation of the accessibility of homepages of the 63 Brazilian Federal Universities. As the use of Content Management Systems (CMS) for the construction of government websites is a recommendation highlighted by e-PWG, this research has also sought to investigate whether these universities are adopting this technology. Given these results, the goal was to identify the use of CMS can contribute or not to create more accessible pages, highlighting the major accessibility problems encountered by these pages.